2022
DOI: 10.1051/0004-6361/202243143
|View full text |Cite
|
Sign up to set email alerts
|

Host galaxy properties of quasi-periodically erupting X-ray sources

Abstract: Context. Quasi-periodic X-ray eruptions (QPEs) are a recently discovered phenomenon, the nature of which remains unclear. Based on their discovery in active galactic nuclei (AGNs), explanations related to an AGN accretion disk or potentially a stellar tidal disruption event (TDE) have been put forward. Alternatives, including highly unequal mass compact object binaries, have also been proposed to explain their properties. Aims. We perform a systematic study of the five known QPE host galaxies with the aim of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 47 publications
3
33
1
Order By: Relevance
“…This mass range is consistent with QPE hosts (Wevers et al 2022), and is also where nuclear star clusters are nearly ubiquitous (e.g., Neumayer et al 2020, for a review), which was confirmed for at least GSN069 (M19; Sheng et al 2021) and RX J1301.9+2747 (Shu et al 2017), and which enhances interactions between the nuclear black hole and stellarmass objects (Rauch 1999;Babak et al 2017;Neumayer et al 2020). At least (but see Wevers et al 2022) the QPE source RX J1301.9+2747 is a young post-starburst galaxy (Caldwell et al 1999), a type in which an enhanced rate of TDEs is observed (e.g., Arcavi et al 2014;French et al 2016) due to higher stellar density (Stone & van Velzen 2016;Stone et al 2018;Law-Smith et al 2017;Hammerstein et al 2021) compared to other much more common types of quiescent galaxies. GSN 069 shows UV line-ratios consistent with a past TDE (Sheng et al 2021), which is also supported by the long-term X-ray emission previous to the QPEs discovery (Shu et al 2018;M19).…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…This mass range is consistent with QPE hosts (Wevers et al 2022), and is also where nuclear star clusters are nearly ubiquitous (e.g., Neumayer et al 2020, for a review), which was confirmed for at least GSN069 (M19; Sheng et al 2021) and RX J1301.9+2747 (Shu et al 2017), and which enhances interactions between the nuclear black hole and stellarmass objects (Rauch 1999;Babak et al 2017;Neumayer et al 2020). At least (but see Wevers et al 2022) the QPE source RX J1301.9+2747 is a young post-starburst galaxy (Caldwell et al 1999), a type in which an enhanced rate of TDEs is observed (e.g., Arcavi et al 2014;French et al 2016) due to higher stellar density (Stone & van Velzen 2016;Stone et al 2018;Law-Smith et al 2017;Hammerstein et al 2021) compared to other much more common types of quiescent galaxies. GSN 069 shows UV line-ratios consistent with a past TDE (Sheng et al 2021), which is also supported by the long-term X-ray emission previous to the QPEs discovery (Shu et al 2018;M19).…”
Section: Introductionsupporting
confidence: 83%
“…QPE have so far been identified in nearby low-mass galaxies (with stellar masses of M star ≈ 1 − few × 10 9 M ; A21). These galaxies host black holes of M BH ≈ 10 5 − few × 10 6 M , as inferred -with the usual large uncertainties -from methods which are both independent (Shu et al 2017;M19;G20;Wevers et al 2022) and dependent on the stellar mass (Strotjohann et al 2016;A21). Given their peak X-ray luminosity (L 0.5−2.0 keV ≈ 10 42 − 10 43 erg s −1 ), the above black hole mass estimates suggest that QPEs peaks are close to being Eddington limited.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, the fifth QPE candidate XMMSL1 J024916.6-041244 showed two QPE-like flares in soft X-rays in 2006 (Chakraborty et al 2021). These QPEs have a coincidence with the galactic nuclei, where all host galaxies are found to be dwarf galaxies with a total stellar mass of around m å ∼ 10 9 M e (Arcodia et al 2021) and black hole (BH) mass of ∼ 10 5−6 M e (e.g., Wevers et al 2022). Interestingly, historical data for GSN 069 shows that it was a quiescent galaxy in 1989, while its X-ray emission was brightened by a factor of at least 240 in 2010 (Miniutti et al 2013;Shu et al 2018).…”
Section: Introductionmentioning
confidence: 84%
“…For those 4 sources the lack of broad emission lines in the optical band is also characteristic, and this feature rules out the possibility to estimate black hole masses independently using broad line diagnostics. As Wevers et al (2022) point out, emission lines noticed in those sources are typical of star-forming or accreting galaxies.…”
Section: Introductionmentioning
confidence: 88%